Early Levosimendan Administration Improved Weaning Success Rate in Extracorporeal Membrane Oxygenation in Patients With Cardiogenic Shock - Chen, Yu-Wen; Lee, Wei-Chieh; Wu, Po-Jui; Fang, Hsiu-Yu; Fang, Yen-Nan; Chen, Huang-Chung; Tong, Meng-Shen; Sung, Pei-Hsun; Lee, Chieh-Ho; Chung, Wen-Jung (Frontiers in Cardiovascular Medicine, 2022)
Background Venoarterial extracorporeal membrane oxygenation (VA-ECMO) has been increasingly used in patients with refractory cardiogenic shock (CS) or out-of-hospital cardiac arrest. It is difficult to perform VA-ECMO weaning, which may cause circulatory failure and death. Levosimendan is an effective inotropic agent used to maintain cardiac output and has a long-lasting effect and may have the potential benefit of levosimendan for VA-ECMO weaning. The study aimed to explore the relationship between the early use of levosimendan and the rate of VA-ECMO weaning failure in patients on VA-ECMO support for circulatory failure. Methods All patients who underwent VA-ECMO in our hospital for CS between January 2017 and December 2020 were recruited in this cohort study and divided into two groups: without and with levosimendan use. Levosimendan was used an add-on other inotropic agent as early as possible after VA-ECMO setting. The primary endpoint was VA-ECMO weaning success, which was defined as survival without events for 24 hours after VA-ECMO withdraw. The secondary outcomes were cardiovascular and all-cause mortality at the 30-day and 180-day follow-up periods post VA-ECMO initialization. Results A total of 159 patients were recruited into our study; 113 patients were enrolled in the without levosimendan use group, and 46 patients were enrolled in the levosimendan use group. In levosimendan use group, the patients received levosimendan infusion within 24 hours after VA-ECMO initialization. Similar hemodynamic parameters were noted between the two groups. Poorer left ventricular ejection fraction and higher prevalence of intra-aortic balloon pumping were observed in the levosimendan group. An improved weaning rate (without vs. with: 48.7% vs. 82.6%; p<0.001) and lower in-hospital mortality rate (without vs. with: 68.1% vs. 43.5%; p=0.007) and 180-day cardiovascular mortality (without vs. with: 75.3% vs. 43.2%; p<0.001) were also noted. Patients administered with levosimendan also presented a lower rate of 30-day (without vs. with: 75.3% vs. 41.3%; p=0.034) and 180-day (without vs. with: 77.0% vs. 43.2%; p<0.001) all-cause mortality. Conclusions Early levosimendan administration may contribute to increase the success rate of VA-ECMO weaning and may help to decrease CV and all-cause mortality.